Empowering Students' Writing Abilities through Interactive Comics: A Vocabulary Achievement - Puspitasari, Ema; Habibul Umam, Lukman; Rosdiani Nasution , Liah (LinguaScopes: International Journal of Language Education, 2025)
Writing is one of the most challenging language skills, requiring strong vocabulary, grammar, and organization. However, many students struggle due to limited vocabulary and lack of engaging instruction. This classroom action research aimed to improve students’ narrative writing through the use of interactive comics. Conducted in two cycles at SMKN 1 Pekalongan with 17 eleventh-grade students, the study followed the stages of planning, action, observation, and reflection. Data were collected through tests, observations, and documentation. In Cycle I, students’ average score increased from 59.12 (pre-test) to 64.62 (post-test), with 37.5% of students reaching the minimum mastery criterion (≥70). In Cycle II, the average score rose to 83.70, with 88.2% of students achieving the target. Observations also showed a significant increase in student participation and engagement. The use of interactive comics not only enhanced vocabulary acquisition in context but also helped students generate ideas and structure their writing more effectively. The findings suggest that comic media is a valuable tool to support vocabulary development and improve students’ writing performance. It also enhanced classroom interaction and teacher performance, making the learning process more dynamic and student-centered.